eHealth in Europe – Status and Challenges - Moen, A.; Hackl, W. O.; Hofdijk, J.; Van Gemert-Pijnen, L.; Ammenwerth, E.; Nykänen, P.; Hoerbst, A. (Yearbook of Medical Informatics, 2013)
Objectives: To present European reflections on the concept of eHealth and emerging challenges related to further development of eHealth in Europe.Methods: A survey with 10 questions was distributed to representatives of the national member associations of the European Federation of Medical Informatics (EFMI).Results: The results document a shift from a constricting ICT-orientation to development of the entire health system where eHealth strategies, organizational change, and appropriate technological infrastructure are singled out as important aspects.Conclusion: There are urgent needs to ensure that eHealth strategies and policies for further design and deployment of eHealth applications support sociable services and innovations in health care.
Keywords: eHealth; status and challenges; Europe; survey